Farmers interest in the use of agricultural machinery services at UPJA Ngupoyo Boga, Mulur Village, Bendosari District, Sukoharjo Regency - Prayoga, Kadhung; Rovita Sum, Ellyana; Mariyono, Joko (AGROMIX, 2025)
Introduction: The Agricultural Machinery Service Business (UPJA) Ngupoyo Boga was the only UPJA in Bendosari District; however, it became inactive between 2020 and 2024 due to incompetent management. This study aimed to identify the factors that shaped farmers' interest and analyze their influence on the use of agricultural machinery services at UPJA Ngupoyo Boga. Methods: The research was conducted from December 2024 to January 2025 in Mulur Village. The method used was a survey with disproportionate stratified random sampling, involving 185 rice farmers. Primary data was obtained through interviews using open and closed questionnaires, while secondary data was taken from previous studies, including books, journals, and official data from relevant institutions. Data analysis was performed descriptively and using multiple linear regression analysis with SPSS 26. Results: The results showed that the factors influencing farmers' interest in Mulur Village regarding the use of agricultural machinery services included gender, age, education level, years of farming, and the size of land owned. The interest variable scored in the moderate category (77.60%), enjoyment in the high category (80.50%), and willingness in the high category (84.07%). The interest, enjoyment, and willingness variables had a significant effect on the use of agricultural machinery services, both simultaneously and partially. Conclusion: Recommendations for UPJA management included developing a routine maintenance schedule, encouraging cooperation among farmers, and suggesting that the government conduct surveys to understand farmers' agricultural machinery needs.